Bacterial Catabolism of Dimethylsulfoniopropionate (DMSP) - Reisch, Chris R.; Moran, Mary A.; Whitman, William B. (Frontiers in Microbiology, 2011)
Dimethylsulfoniopropionate (DMSP) is a metabolite produced primarily by marine phytoplankton and is the main precursor to the climatically important gas dimethylsulfide (DMS). DMS is released upon bacterial catabolism of DMSP, but it is not the only possible fate of DMSP sulfur. An alternative demethylation/demethiolation pathway results in the eventual release of methanethiol (MeSH), a highly reactive volatile sulfur compound that contributes little to the atmospheric sulfur flux. The activity of these pathways control the natural flux of sulfur released to the atmosphere. Although these biochemical pathways and the factors that regulate them are of great interest, they are poorly understood. Only recently have some of the genes and pathways responsible for DMSP catabolism been elucidated. Thus far, six different enzymes have been identified that catalyze the cleavage of DMSP, resulting in the release of DMS. In addition, five of these enzymes appear to produce acrylate, while one produces 3-hydroxypropionate. In contrast, only one enzyme, designated DmdA, has been identified that catalyzes the demethylation reaction producing methylmercaptopropionate (MMPA). The metabolism of MMPA is performed by a series of three coenzyme-A mediated reactions catalyzed by DmdB, DmdC, and DmdD. Interestingly, Candidatus Pelagibacter ubique, a member of the SAR11 clade of Alphaproteobacteria that is highly abundant in marine surface waters, possessed functional DmdA, DmdB, and DmdC enzymes. Microbially mediated transformations of both DMS and methanethiol are also possible, although many of the biochemical and molecular genetic details are still unknown. This review will focus on the recent discoveries in the biochemical pathways that mineralize and assimilate DMSP carbon and sulfur, as well as the areas for which a comprehensive understanding is still lacking.